2018
DOI: 10.1111/jcmm.13658
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MEG3 inhibits the progression of prostate cancer by modulating miR‐9‐5p/QKI‐5 axis

Abstract: This study was designed to detecting the influences of lncRNA MEG3 in prostate cancer. Aberrant lncRNAs expression profiles of prostate cancer were screened by microarray analysis. The qRT‐PCR and Western blot were employed to investigating the expression levels of lncRNA MEG3, miR‐9‐5p and QKI‐5. The luciferase reporter assay was utilized to testifying the interactions relationship among these molecules. Applying CCK‐8 assay, wound healing assay, transwell assay and flow cytometry in turn, the cell proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
110
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(116 citation statements)
references
References 20 publications
6
110
0
Order By: Relevance
“…In this study, to verify the targeting relationship between MEG3, miR-9-5p and MDK, a dual luciferase reporter assay was performed. Consistent with the above reports [9,30], we found MEG3 directly targets miR-9-5p.Subsequently, we demonstrated that MDK is a direct target of miR-9-5p.This finding was in agreement with a previous study reporting that exosomal miR-9 targets MDK in nasopharyngeal carcinoma [15]. Further, we found the expression of miR-9-5p is downregulated, and the expression of MDK is upregulated by MEG3, indicating that MEG3 could regulate the miR-9-5p/MDK axis in HCC.…”
Section: Mmp1 Is Involved In Invasion and Metastasis During The Develsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, to verify the targeting relationship between MEG3, miR-9-5p and MDK, a dual luciferase reporter assay was performed. Consistent with the above reports [9,30], we found MEG3 directly targets miR-9-5p.Subsequently, we demonstrated that MDK is a direct target of miR-9-5p.This finding was in agreement with a previous study reporting that exosomal miR-9 targets MDK in nasopharyngeal carcinoma [15]. Further, we found the expression of miR-9-5p is downregulated, and the expression of MDK is upregulated by MEG3, indicating that MEG3 could regulate the miR-9-5p/MDK axis in HCC.…”
Section: Mmp1 Is Involved In Invasion and Metastasis During The Develsupporting
confidence: 93%
“…LncRNAs and miRNAs could interact with each other to serve a wide spectrum of biological functions [7,8]. MEG3 has been reported to serve as a competing endogenous RNA (ceRNA) for miR-9-5p in prostate cancer [9] and esophageal cancer [10] to mediate tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant study has disclosed the interactions among lncRNA, miRNA, and target genes in the study of tumor mechanism. For instance, lncRNA MEG3 could hinder prostate cancer progression via modulating miR-9-5p/QKI-5 axis [28]. LncRNA MEG3 blocks cell proliferation and induces cell apoptosis in laryngeal cancer through regulating miR-23a/APAF-1 axis [29].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA NEAT1 facilitated oncogene transcription by epigenetic modification of gene promoter in PC-3 and VAaP cells [15]. LncRNA MEG3 sponged miR-9-5p, upregulated QKI-5 and suppressed prostate cancer cell proliferation, migration, invasion and induced apoptosis [16]. Fer-1-like protein 4 (FER1L4) have recently attracted the researchers' attention due to its involvement in the progression of cancer [17,18].…”
Section: Introductionmentioning
confidence: 99%